Susceptibility profiles of helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) to deltamethrin reveal a contrast between the northern and the southern Benin - Tossou, E.; Tepa-Yotto, Ghislain T.; Kpindou, O.K.D.; Sandeu, R.; Datinon, B.; Zeukeng, F.; Akoton, R.; Tchigossou, G.M.; Djègbè, I.; Vontas, J.; Martin, T.; Wondji, C.; et al. (MDPI, 2019)
Helicoverpa armigera is an indigenous species in Africa and has been reported in the destruction of several crops in Benin. Management of H. armigera pest is mainly focused on the use of synthetic pyrethroids, which may contribute to resistance selection. This study aimed to screen the susceptibility pattern of field populations of H. armigera to deltamethrin in Benin. Relevant information on the type of pesticides used by farmers were gathered through surveys. Collected samples of Helicoverpa (F0) were reared to F1. F0 were subjected to morphological speciation followed by a confirmation using restriction fragment length polymorphism coupled with a polymerase chain reaction (RFLP-PCR). F1 (larvae) were used for insecticide susceptibility with deltamethrin alone and in the presence of the P450 inhibitor Piperonyl Butoxide (PBO). Deltamethrin and lambda-cyhalothrin were the most used pyrethroids in tomato and cotton farms respectively. All field-sampled Helicoverpa were found to be H. armigera. Susceptibility assays of H. armigera to deltamethrin revealed a high resistance pattern in cowpea (resistance factor (RF) = 2340), cotton (RF varying from 12 to 516) and tomato (RF=85) farms which is a concern for the control of this major polyphagous agricultural pest. There was a significant increase of mortality when deltamethrin insecticide was combined with piperonyl butoxide (PBO), suggesting the possible involvement of detoxification enzymes such as oxidase. This study highlights the presence of P450 induced metabolic resistance in H. armigera populations from diverse cropping systems in Benin. The recorded high levels of deltamethrin resistance in H. armigera is a concern for the control of this major agricultural pest in Benin as the country is currently embarking into economical expansion of cotton, vegetables and grain-legumes cropping systems.